Nutrition in cachexia: from bench to bedside. Issue 2 (11th March 2016) - Konishi, Masaaki; Ishida, Junichi; von Haehling, Stephan; Anker, Stefan D.; Springer, Jochen
Abstract: As malnutrition is often present in cachexia, nutritional intervention has been one of the widely accepted strategies. A literature review of cachexia models with dietary interventions in the present issue of this journal pointed out that the majority of nutrient intervention studies were of n‐3 fatty acid, mainly eicosapentaenoic acid and docosahexaenoic acid. Effect on protein catabolism and anti‐inflammation are most pronounced benefits of n‐3 fatty acid. The effectiveness of n‐3 fatty acid may depend on control diet or even be attributed to the polyunsaturated fatty acid deficiency inadvertently produced in control group. However, there is not enough clinical evidence to support a benefit of n‐3 fatty acid substitution in patients with cachexia. The second important result from this review is that the majority of studies did not provide information about dietary design or did not standardize design, content, source, and overall composition. To guide dietary design for researchers in preclinical studies, a model has been proposed in this review, which may be useful to predict the efficacy of new dietary intervention in cachexia science. From a clinical point of view, the limited effectiveness of nutritional support in cachexia may partly be explained by the multifactorial nature of this condition. Cachexia differs from malnutrition inasmuch as malnutrition can be reversed by adequate nutrition and/or by overcoming problems of absorption or utilization of nutrients, but cachexia cannot be successfully treated by nutrition alone. Multidisciplinary approach including the assessment and intervention in feeding, appetite, swallowing, exercise, psychosocial, and psychological issue may be needed to improve nutrition in patients with cachexia.